POLITICAL ORIENTATIONS OF THE YOUTH IN TAJIKISTAN,UZBEKISTAN AND KAZAKHSTAN - KABUL, Oralbay; BERKIMBAEVA, Asel; AKHMETOVA, Bigaysha; BERKENOVA, Bibigul (CENTRAL ASIA AND THE CAUCASUS, 2017)
The political systems of Tajikistan, Uzbekistan, and Kazakhstan are complicated and heterogeneous public structures, undergoing difficult and contradictory processes of transformation of all basic institutions, norms, and principles of relationships between themselves and society. Students play a crucial role in this process, which explains why the states want to offer the best possible conditions for the younger generation to help realize its potential in the interests of the state. This dictates changing the system designed to work with young people at all levels of power, as well as the mechanisms of governance. It was not by chance that the youth of these republics has been selected for the studies of political processes unfolding in these republics: young people are normally very critical of political education and training. Young people, due to the high educational level and socio-political activity and dynamic social behavior, will replace, in the near future, the main productive and intellectual public force. However, today there are no adequately developed methodological approaches to the conceptualization of students as a social group and objects of social and political analysis, which means that we should carefully study the experience, problems, and developmental issues in the process of transformation of contemporary post-Soviet society in Tajikistan, Uzbekistan, and Kazakhstan. All aspects of the content and manifestations of political orientations in the youth milieu are being actively discussed in academic writings. Yet, the phenomenon of political orientation—the problem of inner belonging to any specific social and political group, a correct understanding of its role in the life of the entire society, the means of forming ideas about oneself as a member of a definite social and political force—was and remains a challenge.